Avoiding the side effects of electric current pulse application to electroporated cells in disposable small volume cuvettes assures good cell survival. Issue 1 (December 2017) - Grys, Maciej; Madeja, Zbigniew; Korohoda, Włodzimierz
Abstract Background The harmful side effects of electroporation to cells due to local changes in pH, the appearance of toxic electrode products, temperature increase, and the heterogeneity of the electric field acting on cells in the cuvettes used for electroporation were observed and discussed in several laboratories. If cells are subjected to weak electric fields for prolonged periods, for example in experiments on cell electrophoresis or galvanotaxis the same effects are seen. In these experiments investigators managed to reduce or eliminate the harmful side effects of electric current application. Methods For the experiments, disposable 20 μl cuvettes with two walls made of dialysis membranes were constructed and placed in a locally focused electric field at a considerable distance from the electrodes. Cuvettes were mounted into an apparatus for horizontal electrophoresis and the cells were subjected to direct current electric field (dcEF) pulses from a commercial pulse generator of exponentially declining pulses and from a custom-made generator of double and single rectangular pulses. Results More than 80% of the electroporated cells survived the dcEF pulses in both systems. Side effects related to electrodes were eliminated in both the flow through the dcEF and in the disposable cuvettes placed in the focused dcEFs. With a disposable cuvette system, we also confirmed the sensitization of cells to a dcEF using procaine by observing the loading of AT2 cells with calceine and using a square pulse generator, applying 50 ms single rectangular pulses. Conclusions We suggest that the same methods of avoiding the side effects of electric current pulse application as in cell electrophoresis and galvanotaxis should also be used for electroporation. This conclusion was confirmed in our electroporation experiments performed in conditions assuring survival of over 80% of the electroporated cells. If the amplitude, duration, and shape of the dcEF pulse are known, then electroporation does not depend on the type of pulse generator. This knowledge of the characteristics of the pulse assures reproducibility of electroporation experiments using different equipment.